Targeted killing in the Light of International Law - جبار شێخه, ڕێبوار; علی سلیمی, رحمان (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
With the rise of international conflicts, the reasons for and techniques of war have shifted, with conflict parties attempting to eliminate their adversaries using the most recent form of warfare. Targeted killing, as one of the most recent forms of warfare, is now widely used in international conflicts, with the use of drones and targeting individuals under the guise of fighting terrorism, but because these processes are frequently carried out within the borders of other countries, civilians are occasionally victims. Some of them defend it, while others oppose it, claiming that it violates the sovereignty of the countries and the principles of international human law. The lack of a legal foundation in this area that controls the regulatory structure of this issue has further complicated this issue and extended the gap between lawyers and researchers. Without a doubt, the rise of the phenomenon of targeted killings, as well as the lack of a legal basis for organizing, must be stopped, and this issue cannot be left in a legal vacuum.